ChemInform Abstract: Na4La2(CO3)5 and CsNa5Ca5(CO3)8: Two New Carbonates as UV Nonlinear Optical Materials. Issue 40 (30th September 2014) - Luo, Min; Wang, GenXiang; Lin, Chensheng; Ye, Ning; Zhou, Yuqiao; Cheng, Wendan
Abstract Compounds (IV) and (VII) are characterized by single crystal XRD, UV/VIS diffuse reflectance spectroscopy, second harmonic generation measurements, and DFT electronic structure calculations.